Analyzing the Reports of Chemical Poisoning and Pharmacological Toxicity in Cases Presented to the Poison Centre in Basra City, Iraq - Al-Rawaq, Ali M. (Universitas Muhammadiyah Sidoarjo, 2025)
Poisoning remains a major global public health concern, accounting for significant morbidity and mortality, particularly in developing countries where access to toxic agents is common. In Iraq, especially in Basra, cases of acute poisoning are frequent, yet epidemiological data remain limited, hampering effective prevention and management strategies. Despite regional studies, there is insufficient systematic analysis of poisoning trends, types of agents, and demographic risk factors in Basra over recent years. This study aimed to evaluate the prevalence, types, and outcomes of chemical and pharmaceutical poisoning cases reported to the Basra Poison Control Centre over a three-year period (2020–2022). A total of 244 cases were analyzed, with nearly half occurring in children under seven years old, indicating their high vulnerability. Males predominated in 2020 and 2021, while females were more frequently affected in 2022. Drugs were the leading cause of poisoning (171 cases), particularly benzodiazepines (18–29.5%) and paracetamol (15–18.5%). Pesticides, especially organophosphorus compounds and zinc phosphide, were the most common non-pharmaceutical agents in 2020 and 2021, whereas sulfur dioxide gas accounted for 30% of chemical cases in 2022. This is the first comprehensive epidemiological study documenting temporal and demographic variations in poisoning cases in Basra, integrating both pharmaceutical and chemical exposures. The findings highlight the urgent need for stricter drug dispensing regulations, enhanced public awareness, and improved poison control strategies, including antidote availability and healthcare worker training, to reduce the burden of poisoning. Highlights: A total of 244 poisoning cases were reported between 2020–2022, with nearly half involving children under seven years old. Pharmaceuticals, especially benzodiazepines and paracetamol, were the leading causes of poisoning across all years. Pesticides and sulfur dioxide gas were the most common non-pharmaceutical agents, highlighting the need for stricter regulation and preventive strategies.